561. Methicillin-Resistant Staphylococcus aureus is Decreasing in Community-Onset Pediatric Infections Treated at a Mid-Atlantic Health System. (15th December 2022) - Prochaska, Erica; Milstone, Aaron; Sick-Samuels, Anna; Xiao, Shaoming; Schumacher, Christina; Tamma, Pranita; Carroll, Karen C; Gadala, Avi
Abstract: Background: Hospitalizations due to soft tissue methicillin resistant S. aureus (MRSA) infections are decreasing nationally. Analyzing trends in pediatric community-onset (CO) S. aureus infections is needed to inform empiric antibiotic selection in the Emergency Department and outpatient settings. Methods: We identified all cultures growing S. aureus between January 1, 2014 and December 31, 2020 in the Johns Hopkins Hospital microbiology laboratory that services an academic medical center, a mid-level teaching hospital, and a community hospital. Patients were included if they were ≤18 years of age or treated in a pediatric location. Cultures that likely represented colonization, such as nasal swabs, throat swabs, or sputum were excluded. Patients hospitalized within 2 calendar days of culture collection were defined as treated in-hospital. All others were defined as treated outpatient. CO infection was defined as a culture obtained within 3 days of hospitalization or from children not hospitalized. Only the first culture per patient per quarter was included. Cochran Armitage test was used to analyze trends in antibiotic susceptibilities. Results: 3517 cultures obtained from 3078 patients were included. 3208 cultures (91%) were CO. Of CO cultures, 2517 (78.5%) were treated in an outpatient setting and 691 (21.5%) were treated in-hospital. There was a 74% decrease in the number of CO S. aureus cultures during the study period: 751 in 2014 to 191 in 2020. Comparing CO cultures from 2014 and 2020, methicillin susceptibility increased from 59.5% to 67% overall (p = 0.007), 59.4% to 63.8% in outpatient treated cultures (p = 0.07), and 60% to 76% among in-hospital treated cultures (p =0.02). Methicillin susceptibility from CO soft tissue sources remained about 60% during the study period with no significant change in trend. When soft tissue sources were excluded from CO cultures, methicillin susceptibility increased from 61.7% in 2014 to 84.1% in 2020 (p = 0.01). Within CO blood cultures, methicillin susceptibility increased from 86.7% to 92.3% (p = 0.4). Conclusion: In a regional health system, CO pediatric MRSA incidence is decreasing. Although the majority of CO bloodstream S. aureus infections are methicillin susceptible, MRSA continues to cause up to 40% of S. aureus soft tissue infections. Disclosures: Aaron Milstone, MD, Merck: Grant/Research Support Karen C. Carroll, MD, Abbott Diagnostics: Advisor/Consultant|BD Diagnostics: Advisor/Consultant|BD Diagnostics: Grant/Research Support|BioRad, Inc: Grant/Research Support|Meridian Biosciences: Grant/Research Support|Roche Diagnostics: Advisor/Consultant|Scanogen, Inc: Advisor/Consultant|Scanogen, Inc: Grant/Research Support|Thermo Fisher, Inc: Advisor/Consultant.